A comprehensive review on biocompatible film sensor containing natural extract: Active/intelligent food packaging. (November 2022) - Azman, N.H.; Khairul, Wan M.; Sarbon, N.M.
Abstract: This review aims to provide a clear description of the compatibility between the main biopolymer matrix and the reinforcing components in manufacturing active and intelligent packaging film. The incorporation of natural extracts and/or nanomaterial improved the mechanical and barrier performance by increasing the cohesiveness of the biopolymer matrix. Meanwhile, the colour changes were due to the alteration of pH attributed to the pH-sensitivity of the bioactive compounds. This showed the great potential of the additives as a sensor for monitoring the real-time freshness of food products. High inhibitory effect for both Gram-positive and Gram-negative bacteria as well as the escalation of scavenging ability also presented a positive effect on antimicrobial and antioxidant properties of the packaging film. Hence, natural extract and/or nanomaterial showed promising additives in corresponding to the positive influences on sensing ability as well as the functional properties of the active and intelligent packaging film.